1991
DOI: 10.2166/wst.1991.0278
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Fate of PCBs in the North Sea: A Review of Available Data

Abstract: From literature data it is calculated that on an annual basis, 11 to 17 tonnes of PCBs enter the North Sea. Largest sources are the Atlantic Ocean and the atmosphere: together they account for 60-79% of the total input. Sources with greatest impact are the rivers, sewers and sludge. Highest concentrations are found close to the Dutch shore and in the German Bight. The PCB levels result in adverse effects on the seal population in the Wadden Sea. Of the total world PCB production, at least 57% is still in use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Some of these congeners are carcinogenic. A total of 78 PCB congeners out of 209 are chiral, and 19 out of 78 chiral congeners form atropisomers (21)(22)(23)(24)(25)(26)(27)(28). Ahlborg and co-workers (22) reported that non-orthocoplanar PCBs congeners were found to be highly toxic followed by mono-orthocoplanar congeners and least toxic were di-ortho-substituted PCBs.…”
Section: Chiral Pollutants Toxicitymentioning
confidence: 99%
“…Some of these congeners are carcinogenic. A total of 78 PCB congeners out of 209 are chiral, and 19 out of 78 chiral congeners form atropisomers (21)(22)(23)(24)(25)(26)(27)(28). Ahlborg and co-workers (22) reported that non-orthocoplanar PCBs congeners were found to be highly toxic followed by mono-orthocoplanar congeners and least toxic were di-ortho-substituted PCBs.…”
Section: Chiral Pollutants Toxicitymentioning
confidence: 99%
“…Seventy-eight (78) out of 209 congeners of PCBs have axial chirality in their non-planar conformation and 19 form stable enantiomers (atropisomers) due to restricted rotation around the central carbon atom [8] (Table 1). Due to these facts, in last few years, attention has been paid to the toxicity/carcinogenesis of PCBs on marine and terrestrial biota [9][10][11][12][13][14][15]. It has also been reported that the non-ortho coplanar PCBs exhibit the highest toxicity followed by the moderately toxic mono-ortho coplanar congeners, while diortho substituted PCBs turned out to be less toxic (Ahlborg, et al 1994).…”
Section: Polychlorinated Biphenyls (Pcbs)mentioning
confidence: 99%
“…The main source of contamination in the North Sea is through riverine outflows, primarily from the Rhine, Scheldt, and Meuse (The Netherlands), Elbe and Weser (Germany), and Thames (United Kingdom). As a consequence, coastal areas and estuaries are significantly polluted by PCDDs, PCBs, and other persistent organic pollutants [5,6]. In order to monitor the extent of contamination, the Dutch government has stated that the assessment of dredged materials will be based on integrated chemical and biological effect measurements [1,7].…”
Section: Introductionmentioning
confidence: 99%